BERMAIN SAMBIL MEMPELAJARI KOSAKATA PADA PEMBELAJARAN BAHASA INDONESIA UNTUK PENUTUR ASING (BIPA) TINGKAT PEMULA - Syarifah Lubna (Balai Bahasa Kalimantan Barat, 2018)
Indonesian for Nonnative Speakers (BIPA) teaching learning process must be done in a fun way, so that the students feel easier learning Indonesian in a relaxed and natural way. Natural language learning has proven to be more effective for second or foreign language learners, including BIPA students, especially for beginners. The game of guessing words at beginner-level BIPA learners becomes effective for students to remember the vocabulary that is needed or used daily not only to memorize but also to use the vocabulary in everyday conversation.